Actualization of Islamic Monetary Policy in Macro Economic Problem Islam - Robi Mufti (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
At the time of the Prophet Muhammad and Khulafaur Rashidin, monetary policy was implemented without using interest instruments. The Islamic Central Bank requires an interest-free instrument to control monetary economic policy in an Islamic economy. In this case, there are several interest-free instruments that the central bank can use to increase or decrease the money supply. The abolition of the interest system did not hinder the control of the money supply in the economy. The Islamic central bank should pursue its monetary policy to produce a growth in the circulation of money sufficient to finance the potential growth in output over the medium and long term within the framework of stable prices and other socioeconomic goals. The aim is to ensure the right monetary expansion, not too slow and not too fast, but enough to be able to produce adequate growth that can produce equitable welfare for the community. Be realistic and cover the medium and long term. To realize this Islamic goal, it is not only necessary to reform the economy and society in line with Islamic lines, but also requires a positive role for the government and all state policies including fiscal, monetary and income must in sync. Monopolistic practices must be eliminated and every effort must be made to promote all factors capable of producing an increase in goods and services